2020
DOI: 10.26466/opus.644848
|View full text |Cite
|
Sign up to set email alerts
|

Okullarda Akran Zorbalığı: Öğretmen Görüşlerine Göre Nitel Bir Çalışma

Abstract: Bu araştırmanın amacı, ilkokullarda ve ortaokullarda yaşanan akran zorbalığını, öğretmen görüşlerine göre incelemektir Bu araştırma, temel nitel betimsel desen ile yürütülmüştür. Çalışma grubu, ilk ve ortaokullarda görev yapan 26'sı (%81,25) kadın, 6'sı (%18,75) erkek toplam 32 öğretmenden oluşmaktadır. Araştırmada veri toplamak için araştırmacılar tarafından geliştirilen Okullarda Akran Zorbalığı Anketi kullanılmıştır. Ankete araştırmanın amacı, akran zorbalığı ve akran zorbalığının özellikleri hakkında kısa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 70 publications
2
2
0
9
Order By: Relevance
“…In the present research, the participating preschool teachers indicated that the most effective methods for addressing peer bullying are in-class activities and family education. These findings are consistent with the conclusions reached by Çarkıt and Bacanlı (2020), who also studied preschool teachers' perspectives on peer bullying and found that the most effective method, according to teachers, is to provide training for students' families as a preventive measure. Similarly, Atış-Akyol, Yıldız, and Akman ( 2018) found in their study on peer bullying that the most commonly used practice by teachers to counter peer bullying is classroom interventions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present research, the participating preschool teachers indicated that the most effective methods for addressing peer bullying are in-class activities and family education. These findings are consistent with the conclusions reached by Çarkıt and Bacanlı (2020), who also studied preschool teachers' perspectives on peer bullying and found that the most effective method, according to teachers, is to provide training for students' families as a preventive measure. Similarly, Atış-Akyol, Yıldız, and Akman ( 2018) found in their study on peer bullying that the most commonly used practice by teachers to counter peer bullying is classroom interventions.…”
Section: Discussionsupporting
confidence: 90%
“…The research findings indicate that one of the primary attitudes teachers have regarding bullying is to modify classroom management strategies and foster empathy among students. This aligns with the conclusions drawn by Çarkıt and Bacanlı (2020), who found in their study that preschool teachers regarded empathy as one of the most effective approaches in preventing peer bullying within the school environment. Similarly, Atış-Akyol, Yıldız and Akman (2018) stated that the most common attitude among preschool teachers when dealing with peer bullying is to meet with the students' families, counselors, and school administration to address the issue.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Bu araştırmada yapılan görüşmeler sonucunda, öğretmenlerin ve öğrencilerin görüş birliğinde olduğu diğer bir konu okullarında zorbalık olduğudur. Okullarda zorbalığın sıklıkla gözlendiğini belirten pek çok çalışma mevcuttur (Atik, 2006;Çarkıt & Bacanlı, 2020;Genç, 2007;Kartal & Bilgin, 2012;Kepenekçi & Çınkır, 2006;Öztürk vd., 2019;Pişkin, 2006;Polat & Sohbet, 2019;Üstündağ Şener vd., 2015). Bu bakımdan bu çalışma örnekleminin büyük bir kısmının okullarında zorbalığa maruz kalması veya zorbaca davranışları gözlemlemesinin literatür bulguları ile paralel olduğu söylenebilir.…”
Section: Tartışma Ve Sonuçunclassified
“…Literatürde öğrenci ve öğretmenlerin zorbalık algısını inceleyen farklı çalışmaların (Akyol vd., 2018;Bayar, 2018;Çarkıt & Bacanlı, 2020) olduğu görülmüştür. Ancak aynı çevrede bulunan öğretmen ve öğrencilerin zorbalık algılarını eş zamanlı inceleyen ve aynı ortamdaki öğretmen ve öğrencilerin zorba davranışlarla ilgili algı farklılıklarını derinlemesine inceleyen bir çalışmaya rastlanmamıştır.…”
Section: Introductionunclassified